Applications of management science. Vol. 16 - Lawrence, Kenneth D.; Kleinman, Gary (Applications of management science., 2013)
Applications of Management Science, Volume 16 focuses on the application of management science to multiple criteria decision making, data envelopment analysis, and managerial applications. Section A focuses on multiple criteria applications in college course scheduling, offshore windfarms, services in a hospital, portfolio optimization, and balancing a sequence dependent disassembly line. Section B focuses on data envelopment analysis applications of productivity in on-line stores, research libraries, and advertising investment plans. Section C focuses on managerial applications on the effects of aging on food consumption, costs of renewable warrantees, pricing models with group buying, and the improvement of patient flow. This volume will be valuable to those interested in multiple criteria applications, data envelopment analysis applications, and other managerial applications of management science.